Evaluación del desempeño de recubrimientos cerámicos para mejorar la resistencia al desgaste de turbinas tipo Pelton, usadas en centrales a filo de agua. (2020)
Hydroelectric plants on the edge of water do not have the capacity to store energy; therefore, they must generate the available energy, according to the flow available at that time. This type of power station must be projected in its initial designs with a complex of civil works, which help to decant the water that enters the turbine, in order to avoid premature damage to the impeller.